Study on mitigation factors for controlling cost overrun in construction project - Abdullah, Fatehi Mansoor Saad (2018)
The construction industry plays an influential role in the socio-economy of a country. In Malaysia also, the construction industry is one of essential industry participating significantly in the growth of socio-economic development. The construction industry in Malaysia are still facing a significant issue of cost overrun, where only 46.8% of public sector and 37.2% of private sector projects were completed within the specified budget. The issue of cost overrun has become a serious concern to investors, which needs stern attention and in-depth research to put forward solutions to this issue. The objectives of this research are to investigate current mitigation practices for controlling cost overrun in construction projects, to identify mitigation problems for controlling cost overrun in construction projects and to recommend key mitigation factors for controlling cost overrun in construction projects. The research was take place in Johor Bahru the capital of Johor State. The research based on quantitative research by using questionnaire to carry out the research. The questionnaire was designed based on the objectives each objective has ten statements with one option, in order to get accuracy results. A total of 80 questionnaires were gathered from a total of 220 contractors of G7 distributed at Johor Bahru. Data collected was analysed using the Statistical Package for the Social Science 22.0 software. The method of analysis that had being used in this research is percentage, frequency and means score value. There is dissatisfaction about the current mitigation practices for controlling cost overrun. Moreover, the study proves that there are mitigation problems faced by contractors. Furthermore, majority of the respondents agreed to the recommendation provided by the study to control cost overrun. Respondents have been recommended that may will be effectiveness to keep construction project within budget. In conclusion, the research has been introduced and recommended major mitigation factors for controlling cost overrun may will help construction industry achieve project within budget.